Anisotropic effects on crack propagation in pressurized line pipes under running ductile fracture scenarios. (15th May 2021) - Xue, L.; Keim, V.; Paredes, M.; Nonn, A.; Wierzbicki, T.
Abstract: The current analyses present results of running ductile fracture propagation in high strength X100 line pipe steels under the influence of anisotropy. Mechanical anisotropy is commonly available in pipe products as a result of the manufacturing process, especially, those subjected to hot/cold-worked deformation. The outcomes of the present analyses show that its effect on the behavior of running ductile fracture in cracked pipes undergoing depressurization is meaningful. For instance, the Crack-Tip Opening Angle (CTOA) not only exhibits a strong dependence to the pipe's diameter size, but also to the material's anisotropy nature when compared to a hypothetical isotropic material. Moreover, laboratory scale tests such as those performed on Battelle Drop Weight Tear (BDWT) samples provide useful information about initiation of ductile crack propagation when the anisotropy features are taken into account in the material description. Highlights: The anisotropy effect on running ductile fracture problems is addressed by a set of suitable finite element simulations and material modeling. Rate dependent constitutive model implementation for anisotropic elastic–plastic simulation along with anisotropic fracture criterion is presented. Fracture toughness experiments on SENT specimens and dynamic crack propagation tests on BDWT samples serve as basis for material model parameters calibration. CTOA and crack velocity are obtained from pipe simulations of different outer diameter-to-wall-thickness ratios for both conditions: anisotropic and isotropic. The aforementioned quantities clearly exhibit significant differences when compared to each other due to anisotropy effects.